NAVIGASI ROBOT MOBIL DALAM LINGKUNGAN DINAMIK DAN TAK TERSTRUKTUR - Trihatmo, Sardjono (Badan Pengkajian dan Penerapan Teknologi, 2006)
This paper presents mobile robot navigation in an environment that is unstructured, dynamic and not predefined. This navigation is based on continually sensing the local environment. Robot and personnel safety is a dominant and essential requirement for this navigation. Therefore a method for obtaining safe directions in a tessellated map of the environment is introduced. Linear combination of vectors is used to obtain the path that is a compromise between the safest and the shortest path. The path enables a mobile robot to reach its goal directly and safely.